Comparative Study of Feedback Control System when Designing Synthetic Genetic Oscillator (International Journal of Innovative Computing, 2016)
Synthetic biology main focus is to reveal the standard design scheme of natural biological systems through designing and modelling of various synthetic genetic devices or circuits.  Gene regulatory network in natural biological systems has been the main reference used as the basic theory when designing genetic device. With the use of various methods, some genetic devices exhibit oscillatory behavior. However, the main problem when designing devices is to ensure its robustness in terms of device performance. The feedback control system is said to be helpful when designing circuit in electrical engineering study. The same type of control system has also been used in designing synthetic genetic oscillatory device. This study briefly discussed on feedback architecture and design approach used when designing synthetic genetic oscillator.